In-between living and manufactured;an exploratory study onbiobulding components for building design - Akyürek Kıbaş, Berrak (My University, 2021)
Living organisms of nature, such as plants and algae, have often provided innovative solutions for buildings within current environmental degradation in relation to the significant matter of the living components in building design since pre-modern to contemporary architecture. Meanwhile, smart technologies such as automation systems, artificial intelligence, and the internet of things (IoT) have taken place in building design, in addition to the integration of a variety of manufactured components from electrical sockets to domestic appliances into buildings since industrialization. At this point, contemporary studies manifest that emerging technological achievements have also enabled the incorporation of living organisms into the design, thereby living and manufactured components tend to grow towards ‘in-between.’ Accordingly, this ‘in-betweenness’ also introduces itself within building design that is expected to alter the design of building components into ‘biobuilding components.’ xvi Within the rapid and comprehensive growth of technology, the number of biobuilding component examples has been increasing gradually and about to infiltrate into everyday lives and surroundings; however, how building design would be affected by biobuilding components is needed to be elaborated in the building design domain. Therefore, this thesis explores the expected impact (s) of biobuilding components with their possible meaning(s) in building design. The objective of the thesis is to present an explanatory study that yields knowledge of biobuilding components by evaluating their theoretical and practical implications. This leads to exploring the expected impacts of biobuilding components by elaborating on historical, phenomenological, practical, technological, building design, and educational meanings of biobuilding components. While the number of biobuilding components in the industry will increase in the years ahead, this research takes a reliable step forward on this emerging field in the building design domain by enhancing architects’ understanding of biobuilding components.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Biobuilding components; Biobuildings; Sustainability; Building design; Biyo yapı bileşenleri; Biyo bina; Sürdürülebilirlik; Akıllı teknolojiler; Bina tasarımı